2020
DOI: 10.11622/smedj.2019023
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge and beliefs on the use of child car restraints in Singapore: a qualitative study

Abstract: INTRODUCTION Road traffic injuries and fatalities represent a significant public health problem. In Singapore, compliance with appropriate child car restraints (CCRs) is poor. We aimed to understand parental knowledge, beliefs and barriers regarding the use of CCRs. METHODSIn this qualitative study, we conducted five focus group discussions with parents who drive with their children in private cars. Participants were recruited using the KK Women's and Children's Hospital's social media page. Guiding questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Prior studies have not observed child restraint practice in taxis. However, a qualitative study using self-report data investigating parental knowledge did emphasise the need of providing child restraints in taxis, 24 which somewhat support our findings that the non-use of child restraints is more prevalent in taxis, and may become an important target for future interventions. Our results also indicate that compared with those travelling in sedans/saloons, children travelling in SUVs/4WDs have a higher likelihood (OR: 1.31) of using child restraints, which is in line with previous findings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Prior studies have not observed child restraint practice in taxis. However, a qualitative study using self-report data investigating parental knowledge did emphasise the need of providing child restraints in taxis, 24 which somewhat support our findings that the non-use of child restraints is more prevalent in taxis, and may become an important target for future interventions. Our results also indicate that compared with those travelling in sedans/saloons, children travelling in SUVs/4WDs have a higher likelihood (OR: 1.31) of using child restraints, which is in line with previous findings.…”
Section: Discussionsupporting
confidence: 81%
“…30 Given the low use rate of child restraint in taxis, intervention programmes might also include the provision of child restraints for use in taxis, an increase in child restraint installation services, and financial incentives for child restraint use by the government. 24 The third major challenge is the lack of awareness of child restraints, which indicates a need for the launch of education programmes on appropriate child restraint use and seating position of child passengers, especially near hospitals and kindergartens. 31 32 Each of these factors may explain the low child restraint use rate and warrant further exploration of initiatives to promote child restraint practice in Shanghai and China.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In a retrospective cohort of over 2,000 Singapore children with road traffic injuries, more than half were unrestrained, with non-compliance to CCS greatest at infancy. 7 In a subsequent qualitative study, 9 parents of young children cited lack of knowledge on the importance of CCS, and inadequate installation skills as barriers to CCS use; parental suggestions to improve CCS compliance from birth included the hospital as a "crucial touch point" for opportunistic education and assistance with installation. 9 In a local cross-sectional study of parents in a tertiary hospital neonatal unit, a significant proportion thought cradling the baby or using a baby carrier was a safe alternative to a CCS, while only 41% of those planning to return home via a motor vehicle intended to use a CCS.…”
mentioning
confidence: 99%
“…7 In a subsequent qualitative study, 9 parents of young children cited lack of knowledge on the importance of CCS, and inadequate installation skills as barriers to CCS use; parental suggestions to improve CCS compliance from birth included the hospital as a "crucial touch point" for opportunistic education and assistance with installation. 9 In a local cross-sectional study of parents in a tertiary hospital neonatal unit, a significant proportion thought cradling the baby or using a baby carrier was a safe alternative to a CCS, while only 41% of those planning to return home via a motor vehicle intended to use a CCS. 10 This apparent gap in parental knowledge and skills may be addressed by providing information and guidance during the postnatal discharge of newborn infants from the hospital and at the hospital emergency department.…”
mentioning
confidence: 99%
“…Liew et al (6) demonstrated that electric scooter injuries are on the rise and consuming an increasing amount of healthcare resources, while Cha et al (7) studied injuries from all types of personal mobility devices, highlighting that electric bicycle injuries tend to be more severe. Looking specifically at road safety for children, Tan et al (8) performed a qualitative study among parents to understand non-compliance behaviours towards child car restraints in Singapore, highlighting actionable points such as the importance of legal enforcement on the roads and improving installation services for child car restraints. These efforts can be meaningfully harnessed if such data is conveyed to the relevant agencies for policymakers to effect change.…”
mentioning
confidence: 99%